Classroom Teacher Leadership in State Elementary Schools: How Principal Supervision - Yoyok Pujianto; Daeng Ayub Natuna; M. Jaya Adi Putra; Ijayani Ijayani (STAI Hubbulwathan Duri, 2023)
The study's purpose was to determine the effect of the principal’s supervision on the leadership of class teachers. This study used a quantitative approach to the type of research ex post facto. The population in this study were 190 class teachers at State Elementary School Tapung Hulu District, Kampar Regency. The research sample was 129 elementary school class teachers. The technique used to determine the sample was cluster sampling based on the number of elementary schools in Tapung Hulu District, Kampar Regency, which totalled 23 schools. The trial was carried out by taking the remaining sample from elementary school teachers, namely 30 people. Data collection techniques use questionnaires that are distributed using Google Forms. The data analysis technique used descriptive statistical analysis and inferential statistical analysis using the SPSS (Statistics Package for Social Science) Version.23 program. The results showed that there was an influence of the principal's supervision on the leadership of state elementary school teachers in Tapung Hulu District, Kampar Regency. Supervision carried out by the principal regularly and continuously can improve teacher leadership in managing the class. The better the supervision carried out by the principal, the better the leadership of the class teacher, both in carrying out learning in class and in improving his abilities.